2023
DOI: 10.1097/md.0000000000033249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose propofol combined with dexamethasone on the prevention of postoperative nausea and vomiting in gynaecological day surgery under remimazolam-based general anesthesia

Abstract: Background: To observe the effect of low-dose propofol combined with dexamethasone on the prevention of postoperative nausea and vomiting (PONV) in gynaecological day surgery under remimazolam-based general anesthesia.Methods: A total of 120 patients, aged from 18 to 65 years old, American Society of Anesthesiologists grade I or II, were scheduled to undergo hysteroscopy under total intravenous anesthesia. The patients were divided into 3 groups (n = 40 each): dexamethasone plus saline group (DC group), dexame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Propofol is known for its ability to prevent PONV, even when administered in small doses [ 31 33 ]. A recent study demonstrated that a small dose of propofol and dexamethasone in remimazolam-based TIVA effectively prevented PONV [ 34 ]. This was also evident in our empirical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is known for its ability to prevent PONV, even when administered in small doses [ 31 33 ]. A recent study demonstrated that a small dose of propofol and dexamethasone in remimazolam-based TIVA effectively prevented PONV [ 34 ]. This was also evident in our empirical findings.…”
Section: Discussionmentioning
confidence: 99%
“…They considered that the antiemetic effect of Propofol might not be significant in laparoscopic gynaecological surgery, where the stimulation of the cervical vagus nerve is lost [10]. However, with the wide application of Propofol and subsequent studies, it was found that the antiemetic effect of Propofol is not only limited to thyroid surgery, but also to short surgeries [11,12], which also has an antiemetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the dosage to 2.0 mg/kg/h does not provide any additional advantages in terms of antiemetic efficacy. Conversely, administering dexamethasone prior to surgery, specifically at a dose of 8 mg, has been shown to effectively reduce the occurrence of postoperative nausea and vomiting (PONV) in cesarean section patients [7].…”
Section: Introductionmentioning
confidence: 99%